Entre ecos e reflexos: uma autoetnografia das performances de masculinidades online no Grindr - Souza Júnior, João Carvalho de (2021)
In the myth of Echo and Narcissus, Echo was condemned to always repeat the behavior of the others, from words to desires (CARVALHO, 1998). One day, Echo met Narcissus who, in turn, was already in love with his own reflection on the edge of a lake. So, the two experienced a tragic relationship. Echo, who was cursed, was doomed to repeat what she heard from Narcissus, who in turn, in love with himself, heard what Echo repeated as an extension of that narcissistic passion. In social and academic life, we sometimes find ourselves among these echoes and reflections: in the position of Echo, we are doomed to echo discourses (FOULCAULT, 1982), such as gender norms (MISKOLCI, 2016) and their performativity (BUTLER, 2003); meanwhile, as in Narciso's position, dominant discourses reflect on us models on how to act, shaping us from our sexual behaviors (BOURDIEU, 2012) to our academic habits (RAJAGOPALAN, 2010). In this way, in this autoethnographic research (ANDERSON, 2006), I place myself in the position of an Echo-Narcissus, who is aware of her/his mythological curse(s) and who seeks to understand the echoes and reflections of the speeches, standards and disciplines about my own online performance. I analyzed the construction processes of my performances in a geosocial network for men looking for sexual/affective relationships with other men, the Grindr, i.e. I searched for linguistic-semiotic strategies that I used to build myself as a desirable profile in that network. I tried to use Applied Linguistics through a more indisciplinary perspective (MOITA LOPES, 2006) and Queer (BORBA, 2015), crossing academic boundaries whenever necessary in the search to better understand: how heteronormative discourses reflect in language and echo our performances of gender? Between echoes and reflections, between descriptions and analyses, I could see that in the search for acceptance and influenced by discourses and norms, Grindr users try to repeat certain performances that over time contribute to the emergence of acceptable and desirable performative patterns which we keep trying to fit us, giving rise to homonormativities in processes of fitting and disembedding in these patterns.